Study on the Interaction between Low-Viscosity High-Permeability Pregrouting Sealing Material and Coal and Its Application - Yujia Chen; Ao Li; Dingding Yang; Tianyu Liu; Xiaowei Li; Jun Tang; Chenglin Jiang (Advances in Polymer Technology)
In order to ensure the intactness of pressure-measuring boreholes and the accuracy of gas pressure determination, pregrouting treatment with polymer materials is frequently applied to bedding drilling in coal mines. However, the existing polyurethane materials are of high viscosity, low permeability, and poor safety, bringing great difficulties to their field promotion and application. In view of this problem, after optimization and experiments, polylactide polyol/polyether polyol 4110/isocyanate was determined as the target system. Bio-based benzoxazine (Boz-F), red phosphorus, and melamine with a mass ratio of 2 : 1 : 2 were used as the flame retardant, which then underwent mechanical modification by hollow glass bubbles. Finally, the pregrouting material with low viscosity and high permeability was compounded, and its interaction with coal was experimentally studied. The results show that compared with traditional polyurethane, the new material increases the effective consolidation distance in the coal seam by 40% on average. Its permeation radius is also larger than the calculated radius of the plastic softening zone of a borehole. In addition, the strengths of coal-new material consolidated products with different ratios fully surpass those of coal-polyurethane material consolidated products. The enhancement of compressive strength and bending strength is up to 153% and 161%, respectively. The field application indicates that after pregrouting treatment of boreholes in the coal seam with the new material, the borehole formation rate reaches 100%. Therefore, the new material is safe and practical for gas pressure measurement through bedding drilling on site.